Volume 10: Ocean Renewable Energy 2018
DOI: 10.1115/omae2018-77703
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Experimental Uncertainty for a Floating Wind Semisubmersible Under Hydrodynamic Loading

Abstract: The objective of this paper is to assess the sources of experimental uncertainty in an offshore wind validation campaign focused on better understanding the nonlinear hydrodynamic response behavior of a floating semisubmersible. The test specimen and conditions were simplified compared to other floating wind test campaigns to reduce potential sources of uncertainties and better focus on the hydrodynamic load attributes. Repeat tests were used to understand the repeatability of the test conditions and to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…The variation in the results is significant and may be due to both intentional and unintentional actions. Recent work focused on quantifying the uncertainty in the experimental results, to try to better understand the discrepancies, suggests that the differences between simulations and experiments are larger than the experimental uncertainties [148][149][150]. Comparisons against full-scale data have also shown large discrepancies; however, the reasons for these discrepancies are more difficult to discern: difficulties in obtaining information about the exact wind and wave conditions, yaw misalignment, or details of the control system, contribute in addition to limitations in the software or user error [151].…”
Section: Account Of Uncertaintiesmentioning
confidence: 99%
“…The variation in the results is significant and may be due to both intentional and unintentional actions. Recent work focused on quantifying the uncertainty in the experimental results, to try to better understand the discrepancies, suggests that the differences between simulations and experiments are larger than the experimental uncertainties [148][149][150]. Comparisons against full-scale data have also shown large discrepancies; however, the reasons for these discrepancies are more difficult to discern: difficulties in obtaining information about the exact wind and wave conditions, yaw misalignment, or details of the control system, contribute in addition to limitations in the software or user error [151].…”
Section: Account Of Uncertaintiesmentioning
confidence: 99%
“…The shaded region in Figure 9 indicates the error range which can be attributed to sensor noise, the values in Table 2. The orange data points indicate the error range observed across the 5 repetitions for the 10 top peaks, the precision metric used in [18]. As can be seen in Figures 8 and 9, the magnitude of the error range is not well correlated to the magnitude of the value being measured with 8 of the top 10 peak error range values being exceeded for at least 85% of the 10-min time concurrent time series for Group B in pitch.…”
Section: Precision Assessment Methodsmentioning
confidence: 97%
“…There are exceptions to this trend of omitting an assessment of experimental uncertainty in FOWT test campaigns. Most notably, in a recent paper [18], the subject of which is a test campaign on the OC5-DeepCwind semisubmersible platform at a scale of 1:50. The authors followed the uncertainty assessment guidelines provided by ASME [5], identified all potential sources of experimental uncertainty, and quantified some examples, such as wave elevation, model centre of gravity determination, platform motions, and mooring line loads.…”
Section: Uncertainty Assessmentmentioning
confidence: 99%
See 2 more Smart Citations